2021
DOI: 10.3389/fonc.2021.671416
|View full text |Cite
|
Sign up to set email alerts
|

A PD-1 Inhibitor Induces Complete Response of Advanced Bladder Urothelial Carcinoma: A Case Report

Abstract: The prognosis of patients with advanced urothelial carcinoma is dismal. Platinum-based chemotherapy is still the main first-line treatment for advanced urothelial carcinoma, while immunotherapy can be used as a first-line treatment option for people who cannot tolerate platinum. Immunotherapy is preferred in the second-line treatment of bladder urothelial carcinoma. PD-1 inhibitors (Pembrolizumab, nivolumab and atezolizumab) and PD-L1 inhibitors (Ddurvalumab and avelumab) have not been approved for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(26 reference statements)
0
5
0
Order By: Relevance
“… 22 Finally, a patient with metastatic bladder cancer achieved CR sustained over 1 year, after four administrations of sintilimab. 23 No comparable response regarding reports of cases with HNSCC were identified. In addition, the case presented here remains unique due to the long duration of sustained CR.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Finally, a patient with metastatic bladder cancer achieved CR sustained over 1 year, after four administrations of sintilimab. 23 No comparable response regarding reports of cases with HNSCC were identified. In addition, the case presented here remains unique due to the long duration of sustained CR.…”
Section: Discussionmentioning
confidence: 99%
“…observed that following treatment with gemcitabine, a patient who had advanced urothelial carcinoma exhibited disease progression. The patient experienced long-term complete remission after receiving only a domestic PD-1 inhibitor (sintilimab) ( 12 ). Fukuta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection in combination with chemotherapy is recognized as the optimal treatment for this lethal malignancy, the long-term survival remains unsatisfactory owing to the late detection, early recurrence, and aggressive biological manner of the tumor ( 8 ). In recent years, immunotherapy with immune checkpoint inhibitors (ICIs) has shown beneficial effects and good safety for various solid cancers including non-small cell lung cancer ( 9 ), gallbladder carcinosarcoma ( 10 ), bladder urothelial carcinoma ( 11 ), colorectal adenocarcinoma ( 12 ), etc. For gastric cancer, immunotherapy has also drastically improved the treatment options in the advanced phase, especially for chemorefractory gastric cancer ( 4 , 13 ).…”
Section: Introductionmentioning
confidence: 99%